Prehospital emergency anaesthesia: an updated survey of UK practice with emphasis on the role of standardisation and checklists. Issue 9 (24th May 2018) - Burgess, Mark R; Crewdson, Kate; Lockey, David J; Perkins, Zane B
Abstract : Introduction: Prehospital emergency anaesthesia (PHEA or 'prehospital rapid sequence intubation') is a high-risk procedure. Standard operating procedures (SOPs) and checklists within healthcare systems have been demonstrated to reduce human error and improve patient safety. We aimed to describe the current practice of PHEA in the UK, determine the use of checklists for PHEA and describe the content, format and layout of any such checklists currently used in the UK. Method: A survey of UK prehospital teams was conducted to establish the incidence and conduct of PHEA practice. Results were grouped into systems delivering a high volume of PHEA per year (>50 PHEAs) and low volume (≤50 PHEAs per annum). Standard and 'crash' (immediate) induction checklists were reviewed for length, content and layout. Results: 59 UK physician-led prehospital services were identified of which 43 (74%) participated. Thirty services (70%) provide PHEA and perform approximately 1629 PHEAs annually. Ten 'high volume' services deliver 84% of PHEAs per year with PHEA being performed on a median of 11% of active missions. The most common indication for PHEA was trauma. 25 of the 30 services (83%) used a PHEA checklist prior to induction of anaesthesia and 24 (80%) had an SOP for the procedure. 19 (76%) of the 'standard' checklists and 5 (50%) of the 'crash' induction checklists used were analysed. On average, standard checklists contained 169 (range: 52–286) words and 41 (range: 28–70) individual checks. The style and language complexity varied significantly between different checklists. Conclusion: PHEA is now performed commonly in the UK. The use of checklists for PHEA is relatively common among prehospital systems delivering this intervention. Care must be taken to limit checklist length and to use simple, unambiguous language in order to maximise the safety of this high-risk intervention.